PENINGKATAN HASIL BELAJAR PEMBELAJARAN JARAK JAUH MATERI TEKS EKSPLANASI MENGGUNAKAN MODEL DIRECT INSTRUCTION BERBASIS KELOMPOK DENGAN MEDIA AUDIOVISUAL - Juminah Juminah (Intersections, 2022)
The research aims to increase the interest and learning outcomes of class VI students at SDN 1 Kedungasem Sumber District semester 1 of the 2021/2022 academic year through the application of a group-based direct instruction model. This type of research is Classroom Action Research. The research subjects were 15 students. Data collection techniques using tests, observation and documentation. Data validation with triangulation techniques. The analysis technique is descriptive quantitative and qualitative. The results showed an interest in learning the initial conditions of 3 students (20%), to 9 students (60%) in the first cycle, and 13 students (87.50%) in the second cycle. The increase in learning outcomes was 56.67, an increase of 66.67 and in the second cycle of 78.33, with the learning mastery of 3 students (20%) in the initial study, 60% or 9 students, and in the last cycle it became 87.50%, or 13 students out of 15 students.